A Narrative Review of Health-Seeking Behaviour in Malaysia: Factors and Emerging Themes - Dayang Hajyrayati, Awg Kassim; Siti Zaleha, Raduan; Rasidah, Abd Wahab (Research and Scientific Innovation Society, 2023)
This article provides a critical assessment of research on health-seeking behaviour in Malaysia. As the topic is both medically and anthropologically relevant, this narrative review aims to collate and synthesise anthropological and medical studies conducted in Malaysia on health-seeking behaviour among different populations in the country. The specific goal of this narrative review is to identify the methodology employed in such studies, compile a list of medical conditions for which health-seeking behaviour has been researched, identify health-seeking barriers or determinants across studies, and highlight emerging trends in related research. Multiple databases were used to search for published materials on this topic by Malaysian researchers, such as PubMed, Scopus, and My Jurnal. A total of 39 studies were included in this review. 29 studies utilised quantitative designs, while the remaining studies utilised mixed-method and qualitative designs. Non-communicable diseases were studied more frequently than communicable diseases. The majority of reviewed studies were conducted in Peninsular Malaysia, with very few studies focusing on the populations of Sabah and Sarawak in East Malaysia. While all of the studies highlight the multidimensional factors that influence health-seeking behaviour in the context of Malaysia, the utilisation of technology for accessing health-related information and COVID-19-related studies has been identified as an emerging trend in the literature on health-seeking behaviour in this country